High modulus regenerated cellulose fibers spun from a low molecular weight microcrystalline cellulose solution - Zhu, Chenchen; Richardson, Robert M.; Potter, Kevin D.; Koutsomitopoulou, Anastasia F.; van Duijneveldt, Jeroen S.; Vincent, Sheril R.; Wanasekara, Nandula D.; Eichhorn, Stephen J.; Rahatekar, Sameer S. (American Chemical Society, 2016)
We have developed a novel process to convert low molecular weight microcrystalline cellulose into stiff regenerated cellulose fibers using a dry-jet wet fiber spinning process. Highly aligned cellulose fibers were spun from optically anisotropic microcrystalline cellulose/1-ethyl-3-methylimidazolium diethyl phosphate (EMImDEP) solutions. As the cellulose concentration increased from 7.6 to 12.4 wt %, the solution texture changed from completely isotropic to weakly nematic. Higher concentration solutions (>15 wt %) showed strongly optically anisotropic patterns, with clearing temperatures ranging from 80 to 90 °C. Cellulose fibers were spun from 12.4, 15.2, and 18.0 wt % cellulose solutions. The physical properties of these fibers were studied by scanning electron microscopy (SEM), wide angle X-ray diffraction (WAXD), and tensile testing. The 18.0 wt % cellulose fibers, with an average diameter of ∼20 μm, possessed a high Young’s modulus up to ∼22 GPa, moderately high tensile strength of ∼305 MPa, as well as high alignment of cellulose chains along the fiber axis confirmed by X-ray diffraction. This process presents a new route to convert microcrystalline cellulose, which is usually used for low mechanical performance applications (matrix for pharmaceutical tablets and food ingredients, etc.) into stiff fibers which can potentially be used for high-performance composite materials.
Keywords: Alignment; Anisotropy; Fiber spinning; Ionic liquid; Mechanical property; Microcrystalline cellulose